2002
DOI: 10.1007/s00467-001-0776-z
|View full text |Cite
|
Sign up to set email alerts
|

In utero exposure to immunosuppressive drugs: experimental and clinical studies

Abstract: Over the last few decades, the number of pregnant women under immunosuppressive (IS) therapy following transplantation or autoimmune diseases has increased. At first, IS drugs, including prednisone, azathioprine, and cyclosporine A were used, but now new molecules such as tacrolimus and mycophenolate mofetil have appeared. These IS drugs cross the placental barrier and enter into the fetal circulation, which poses a risk for fetal development. Experimental data have shown that IS drugs often have deleterious e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
86
1
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(89 citation statements)
references
References 63 publications
1
86
1
1
Order By: Relevance
“…CsA is thus used in pregnant patients for its graft and life-saving immunosuppressive effects despite the fact that it induces intrauterine growth retardation in over half of the pregnancies after renal and liver transplants (30). Short-term studies did not reveal any adverse effect of in utero exposure to CsA on renal function of the children born to female transplant recipients (31).…”
Section: Figurementioning
confidence: 99%
“…CsA is thus used in pregnant patients for its graft and life-saving immunosuppressive effects despite the fact that it induces intrauterine growth retardation in over half of the pregnancies after renal and liver transplants (30). Short-term studies did not reveal any adverse effect of in utero exposure to CsA on renal function of the children born to female transplant recipients (31).…”
Section: Figurementioning
confidence: 99%
“…Such agents have also been shown to have an effect on renal development, especially mycophenolate mofetil (45,46). The pathways involved have not been clarified thus far, but a recent study has identified two factors involved: PDGF-B, potently inducing proliferation, and early growth response gene-1, a transcription factor (47).…”
Section: Drugs Disturbing Renal Developmental Factorsmentioning
confidence: 99%
“…However, the concentration in fetal blood is much lower, and is 1-5% of that in the maternal serum [14][15][16]. Cyclosporine A cross the placenta, reaching about 5% fetal blood concentration compared to the concentration in the maternal serum [14][15][16][17][18]. Systematic literature review published in 2016 by the European League Against Rheumatism shows compatibility with pregnancy and lactation for azathioprine, cyclosporine, tacrolimus and glucocorticosteroids [19].…”
Section: Discussionmentioning
confidence: 99%